Decreased Thalamic Activity Is a Correlate for Disconnectedness during Anesthesia with Propofol, Dexmedetomidine and Sevoflurane But Not S-Ketamine - Kantonen Oskari; Laaksonen Lauri; Alkire Michael; Scheinin Annalotta; Långsjö Jaakko; Kallionpää Roosa E.; Kaisti Kaike; Radek Linda; Johansson Jarkko; Laitio Timo; Maksimow Anu; Scheinin Joonas; et al. (SOC NEUROSCIENCE, 2025)
Establishing the neural mechanisms responsible for the altered global states of consciousness during anesthesia and dissociat-ing these from other drug-related effects remains a challenge in consciousness research. We investigated differences in brain activity between connectedness and disconnectedness by administering various anesthetics at concentrations designed to render 50% of the subjects unresponsive. One hundred and sixty healthy male subjects were randomized to receive either propofol (1.7 lg/ml; n= 40), dexmedetomidine (1.5 ng/ml; n= 40), sevoflurane (0.9% end-tidal; n= 40), S-ketamine (0.75 lg/ml; n= 20), or saline placebo (n = 20) for 60 min using target-controlled infusions or vaporizer with end-tidal monitoring. Disconnectedness was defined as unresponsiveness to verbal commands probed at 2.5-min intervals and unawareness of external events in a postanesthesia interview. High-resolution positron emission tomography (PET) was used to quantify regional cerebral metabolic rates of glucose (CMRglu) utilization. Contrasting scans where the subjects were classified as connected and responsive versus disconnected and unresponsive revealed that for all anesthetics, except S-ketamine, the level of thalamic activity differed between these states. A conjunction analysis across the propofol, dexmedetomidine and sevoflurane groups confirmed the thala-mus as the primary structure where reduced metabolic activity was related to disconnectedness. Widespread cortical metabolic suppression was observed when these subjects, classified as either connected or disconnected, were compared with the placebo group, suggesting that these findings may represent necessary but alone insufficient mechanisms for the change in the state of consciousness.